Development of a Peer Support Model Using Experience-Based Co-Design to Improve Critical Care Recovery. (March 2019) - Haines, Kimberley J.; Holdsworth, Clare; Cranwell, Kathryn; Skinner, Elizabeth H; Holton, Sara; MacLeod-Smith, Belinda; Bates, Samantha; Iwashyna, Theodore J.; French, Craig; Booth, Sarah; Carmody, Jacki; Henningham, Lucy; et al.
Abstract : Objectives: To use experience-based co-design to identify the key design requirements of a peer support model for critical care survivors; understand the use of the experience-based co-design method from clinician, patients, and family perspectives. Design: Using experience-based co-design, qualitative data about participants' preferences for a peer support model were generated via workshops. Participants' perspectives of experience-based co-design were evaluated with focus groups. Setting: University-affiliated hospital in Melbourne, Australia. Subjects: Snowball sampling was used to recruit clinicians from across the care spectrum (ICU-community); critical care survivors and nominated family members were recruited using convenience sampling. Measurements and Main Results: Consensus on a peer support model was reached through the experience-based co-design process, with the following key themes: 1) socialization and group cohesion; 2) management of potential risks; and 3) individualized needs of patients and families. Evaluation of participants' perspectives of the experience-based co-design method identified five key themes: 1) participation as a positive experience; 2) emotional engagement in the process; 3) learning from patients and family members; 4) feeling heard; and 5) practical challenges of experience-based co-design and readiness to participate. Conclusions: Experience-based co-design was a feasible approach to developing a peer support model for use with critical care survivors and was well received by participants. Future testing of the co-designed peer support model in a pilot randomized controlled trial will enhance understanding of peer support in critical care and the use of experience-based co-design as a design methodology. Abstract : Supplemental Digital Content is available in the text.